The Differences Of Student’s Achievement Between Using Cooperative Model Type Kancing Gemerincing and Time Token on Environment Pollution Concept - Mufti Ali (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2016)
The purpose of this research is to describe the difference of student’s achievement cognitive, affective, and psychomotor on natural science subject between cooperative learning model with kancing gemerincing type and time token type. Which one’s better, the student’s cognitive, affective, and psychomotor on environment pollution concept between cooperative learning model with kancing gemerincing type and time token type. This research used pre experimental design method, which is the population is all of the seventh grade students of SMP Negeri 8 Tasikmalaya. Sample total entire 2 class that is class VIIA and VIID with each student as much 35 person. Measurement uses post test. Analysis technique that used t-independent on level of significant α = 0,05. The result shows that found the difference of student’s achievement cognitive, affective, and psychomotor on environment pollution concept between cooperative learning model with kancing gemerincing type and time token type. Based on the result in above it can be said student’s achievement cognitive, and psychomotor by using kancing gemerincing type model was better than time token type model on environment pollution concept. Beside that student’s achievement affective by using time token type model was better than kancing gemerincing type model on environment pollution concept.